Evaluation of Seismic Response of Multi-Story Structures: A Comparative Study of Buckling Restrained Braces and Viscous Dampers (Journal of Civil Engineering Researchers, 2025)
In buckling restrained bracing systems, earthquake-induced elongation problems are solved, and BRB-equipped structures have a much more effective performance in energy absorption in addition to high lateral stiffness. Systems equipped with viscous dampers (VD) also have great potential to absorb seismic energy. To assess the vulnerability of structures equipped with buckling restrained bracing (BRB) and VD systems, three structures (6-, 10- and 15-story) were chosen as representatives of mid-rise, high-rise and super high-rise buildings and modeled in four states of moment-resisting frame (MRF): the frame equipped with VD, the frame equipped with BRB, and the frame equipped with BRB and viscous damper simultaneously (BRB+VD) using OpenSees-2.4.6 software under incremental dynamic analysis (IDA). Seven seismic records were applied, and the maximum inter-story drift response and fragility curves were determined. The results indicated that although the simultaneous application of BRB+VD causes a significant decline in the response of all structures, each of these two systems is able to provide structural safety at various levels in mid-rise structures. It is required to apply both systems simultaneously to provide safety for slight and moderate levels of damage in high-rise buildings, while super high-rise buildings are vulnerable to whole levels of damage, and their structural safety involves the simultaneous use of both systems.
Keywords: Viscous Damper; Buckling Restrained Brace; Incremental Dynamic Analysis; Seismic Response; Multi-Story Structures